SUSTAINABLE BUSINESS PRACTICES, FINANCIAL LITERACY, AND ENTREPRENEURIAL ORIENTATION ON MSME GROWTH - Purwanti, Ari; Zaman, Delfian; Hidayati, Nur; Basir, Badirun (Indo-Fintech Intellectuals: Journal of Economics and Business, 2025)
This study examines the impact of sustainable business practices, financial literacy, and entrepreneurial orientation on the growth of Micro, Small, and Medium Enterprises (MSMEs). Utilizing a quantitative research approach, data were collected from MSME owners and analyzed using multiple regression techniques. The results indicate that all three factors significantly contribute to MSME growth, with financial literacy emerging as the strongest predictor. Sustainable business practices enhance operational efficiency and market reputation, while entrepreneurial orientation fosters innovation and competitive advantage. The findings underscore the importance of integrating financial education, sustainability initiatives, and entrepreneurial strategies to ensure long-term business success. This study provides valuable insights for MSME owners, policymakers, and financial institutions in developing targeted support programs. Future research should explore moderating factors and conduct cross-country analyses to enhance the generalizability of these findings.